Aftereffect and Reproducibility of Three Excitatory Repetitive TMS Protocols for a Response Inhibition Task - Ji, Gong-Jun; Wei, Jun-Jie; Liu, Tingting; Li, Dandan; Zhu, Chunyan; Yu, Fengqiong; Tian, Yanghua; Wang, Kai; Zhang, Lei; Hu, Panpan (Frontiers in Neuroscience, 2019)
A number of repetitive transcranial magnetic stimulation (rTMS) protocols have been developed for modulating brain function noninvasively. To screen out the most powerful one, these protocols has been compared in the context of the motor system. However, to which extent the conclusions could be generalized to high-level systems is largely unknown. In this study, we compared the modularity ability of three excitatory rTMS protocols on high-level cognition represented by response inhibition ability. In the first experiment, we found that intermittent theta-burst stimulation (iTBS) could significantly improve the stop signal reaction time in the stop signal task, while 5-Hz and 25-Hz stimuli were ineffective. This iTBS effect was significantly higher than the sham simulation, and only occurred in the second session of stop signal task after iTBS in the first experiment. However, this aftereffect of iTBS was not reproduced in the second experiment, implicating high variability across subjects. In summary, our findings indicated a possible improving effect of iTBS on response inhibition ability, but its reproducibility needs further investigation.